Jews, Real and Imagined, at San Isidoro de León and Beyond - Harris, Julie A. (2019)
From the tenth to the fifteenth centuries, medieval León possessed a thriving Jewish community whose presence can be traced via archaeological and documentary remains. As regards the treasury of San Isidoro de León, however, there is no evidence for the involvement of living Jews with its luxury objects—an involvement that has been documented in comparable centers elsewhere in Iberia and Europe. Apart from a possible but unproven relationship to its textiles, a Jewish connection to the Treasury of San Isidoro remains ideological and limited to the presence of Abraham's relics in a single treasury object. However, both living and ideological Jews can be associated with León's cathedral, where a portion of the Jewish community's annual taxes was earmarked to light its altars and where the sculptural program featured the blind synagogue.
Keywords: Jews; León; San Isidoro (León); Toledo; Urraca; Relics; synagogue of León; Textiles